Exploring genre representation in English textbooks: implications for curriculum, textbook and literacy development - Turgut Dost, Guliz (Frontiers in Education, 2025)
IntroductionTextbooks are vital tools for exposing learners to diverse genres, allowing them to explore various texts formats and styles, and developing genre awareness through reading texts.MethodsThis qualitative study investigated the representation and frequency of genres within 7–12 grade English textbooks by situating its analysis within the framework of Systemic Functional Linguistics. Utilizing document analysis, the study evaluated a total of 114 texts from the English textbooks published by Turkish Ministry of National Education.ResultsFindings reveal that report genre constitutes the most prominent genre, with descriptive reports being the most frequently encountered subcategory. Argumentation follows as the second most modeled genre, followed by recounts. However, macro genres, procedures, and narratives are underrepresented. Along with the underrepresented genres, there are also significant disparities in the exposure to genre subcategories, suggesting that while foundational genres are cultivated, there remains an over-reliance on specific genres at the expense of diversity. The results further reveal a gradual increase in genre complexity and diversity through grades, excluding a notable decline in diversity at the 9th and 10th grades.DiscussionThis study underscores the importance of diversifying genre representation in K-12 English textbooks and offers recommendations for curriculum developers and educators to enhance genre awareness and literacy skills among English language learners.